Change of clinical indices in patients with the dry form of age-related macular degeneration (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Age-related macular degeneration (AMD) is a frequent cause of irreversible blindness in persons of advanced age and possesses high prevalence and propensity to progressing.Material and methods. Disturbances of clinical indices in 108 patients with the dry form of age-related macula degenerations was investigated.Results. Visual acuity in patients of the basic group was 0.53+0.06 that was lower (p
Keywords: age-related macular degeneration (AMD); clinical indices